Pengukuran Loyalitas Konsumen Produk Perhiasan Mutiara Kota Mataram - Ilhamudin, Muhammad; Rusminah, Rusminah; Hilmiati, Hilmiati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study aims to analyze customer loyalty towards Sekarbela pearl jewelry, a leading product of Mataram City. Using a descriptive approach, the study measures loyalty as a key aspect of consumer behavior. A sample of 100 respondents was purposively selected from customers at several sales points in Mataram City, including the craft center, city outlets, and street vendors. Data analysis was conducted using the Net Promoter Score (NPS) model. The results show variation in loyalty levels based on purchase location. Customers at the Sekarbela craft center are categorized as highly loyal, while buyers at city outlets and street vendors are categorized as loyal. This loyalty is built through positive perceptions of product attributes such as pearl quality, aesthetics, durability, framing materials, specification suitability, and price. The high perception of product performance encourages customers to recommend the product to others. These findings underscore the importance for marketers to maintain and enhance loyalty to ensure the future sustainability of the Sekarbela pearl jewelry business.